(untitled) (diségno, 2025)
The relationship between drawing and language is a theme widely frequented by the theory and critical history of drawing discipline as well as by the disciplines that are adjacent to it or that refer to it: I am thinking of the disciplines of design and those of the artistic sphere, I am thinking of the history of art, representation, graphics, I am thinking of semiotics, philosophy, etc. It is an ancient relationship that, from time to time, reveals similarities, points of contact, overlaps. [read more]